1995
DOI: 10.1002/mrd.1080420215
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the chromosome complement of frozen‐thawed mouse oocytes after parthenogenetic activation

Abstract: Frozen-thawed mouse oocytes were artificially activated with Sr2+ and analyzed cytogenetically at the first cleavage division to examine the behavior of the maternal chromosomes independently of the paternal complement. There was no significant difference in the rate of activation between frozen-thawed and freshly collected oocytes and the majority of oocytes (> 90%) had a normal haploid chromosome constitution. The incidence of second polar body retention in frozen-thawed oocytes was low and did not differ si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…However, the majority of studies with frozen-thawed mouse oocytes have not found any significant increase in the frequency of aneuploidy at first cleavage metaphase after fertilization in vitro [6,20]. Recently, we have confirmed this with frozenthawed mouse oocytes, where parthenogenetic activation of the oocytes with Sr 2+ was used to study the behavior of the maternal chromosomes in the absence of the paternal complement [21].…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…However, the majority of studies with frozen-thawed mouse oocytes have not found any significant increase in the frequency of aneuploidy at first cleavage metaphase after fertilization in vitro [6,20]. Recently, we have confirmed this with frozenthawed mouse oocytes, where parthenogenetic activation of the oocytes with Sr 2+ was used to study the behavior of the maternal chromosomes in the absence of the paternal complement [21].…”
Section: Introductionmentioning
confidence: 62%
“…The combined effects of the components of VSI or exposure to the cryoprotectants at room temperature for 15 min may have disrupted the spindle more profoundly than in the present study. In oocytes exposed to 1.5 M DMSO at 37 0 C for 1 h, the incidence of aneuploidy after parthenogenetic activation is increased significantly [21]. However, the data of Kola et al [14] show a preponderance of hypohaploid spreads, which may have resulted from the loss of chromosomes during preparation.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The introduction of intracytoplasmic sperm injection made it possible to overcome zona hardening after cryopreservation (6). Furthermore, subsequent studies suggest that the spindle is capable of undergoing some repair after cryopreservation and that dispersed chromosomes are rare (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 98%